Visual cocaine detection with gold nanoparticles and rationally engineered aptamer structures - Zhang, Juan (2012)
A novel bioassay strategy is designed to detect small-molecule targets such as cocaine, potassium, and adenosine, based on gold nanoparticles (AuNPs) and engineered DNA aptamers. In this design, an aptamer is engineered to be two pieces of random, coil-like single-stranded DNA, which reassembles into the intact aptamer tertiary structure in the presence of the specific target. AuNPs can effectively differentiate between these two states via their characteristic surface-plasmon resonance-based color change. Using this method, cocaine in the low-micromolar range is selectively detected within minutes. This strategy is also shown to be generic and applicable to the detection of several other small-molecule targets.